Advancements in Gas Separation for Energy Applications: Exploring the Potential of Polymer Membranes with Intrinsic Microporosity (PIM) - Carmela Astorino; Eugenio De Nardo; Stefania Lettieri; Giuseppe Ferraro; Candido Fabrizio Pirri; Sergio Bocchini (Membranes, 2023)
Membrane-based Polymers of Intrinsic Microporosity (PIMs) are promising candidates for energy-efficient industrial gas separations, especially for the separation of carbon dioxide over methane (CO2/CH4) and carbon dioxide over nitrogen (CO2/N2) for natural gas/biogas upgrading and carbon capture from flue gases, respectively. Compared to other separation techniques, membrane separations offer potential energy and cost savings. Ultra-permeable PIM-based polymers are currently leading the trade-off between permeability and selectivity for gas separations, particularly in CO2/CH4 and CO2/N2. These membranes show a significant improvement in performance and fall within a linear correlation on benchmark Robeson plots, which are parallel to, but significantly above, the CO2/CH4 and CO2/N2 Robeson upper bounds. This improvement is expected to enhance the credibility of polymer membranes for CO2 separations and stimulate further research in polymer science and applied engineering to develop membrane systems for these CO2 separations, which are critical to energy and environmental sustainability. This review aims to highlight the state-of-the-art strategies employed to enhance gas separation performances in PIM-based membranes while also mitigating aging effects. These strategies include chemical post-modification, crosslinking, UV and thermal treatment of PIM, as well as the incorporation of nanofillers in the polymeric matrix.